Prevalence of Subthreshold Depression Among Constipation-Predominant Irritable Bowel Syndrome Patients - Mokhtar, Norfilza Mohd; Bahrudin, Mohd Fyzal; Abd Ghani, Nazierah; Abdul Rani, Rafiz; Raja Ali, Raja Affendi (Frontiers in Psychology, 2020)
Patients suffering from irritable bowel syndrome (IBS) may have some form of affective disorders that may worsen their symptoms. Lack of screening among IBS patients is one of the reasons for depression unawareness among healthcare providers. The present study was conducted to evaluate the prevalence of depression among patients with constipation-predominant IBS. A total of 240 IBS patients who fulfilled Rome III criteria were enrolled. The psychiatric assessment was evaluated using the Center for Epidemiologic Studies Depression Scale Revised (CESD-R). Twenty items in CESD-R scale measured symptoms of depression in nine separate groups. Patients were categorized into five different subgroups: major depressive episode, probable major depressive episode, possible major depressive episode, subthreshold depressive symptoms and without clinical significance of depression. Out of the 240 patients with constipation-predominant IBS, the majority (n=161, 67.1%) had no clinical significance of depression. Seventy seven (32.1%) had subthreshold depression and only two (0.83%) patients were regarded as having probable a major depressive episode. No patient was categorized into a major or possible major depressive episode. The prevalence of subthreshold depression was the highest among female (72.3%) patients with 51.1% being single, 44.7% were married and 4.3% were divorcees. When stratified according to ethnicity, subthreshold depression was highly prevalent among Malays (76.6%), followed by Chinese (19.2%) and Indians (2.1%). A high percentage of the patients were found to be non-smokers (93.6%) and had lower income of less than RM 5000 (USD 1250) per month (89.4%). The moderately high prevalence of subthreshold depression among patients with IBS, justifies psychological evaluation in all patients with functional gastrointestinal disorders.